Modern optical approaches in the modulation of eye growth: a new era in the control of childhood myopia - Mirković, Andrea; Savić, Nikola (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Myopia among preschool and school-aged children represents a growing public health concern, closely linked to reduced exposure to natural light and excessive use of digital devices. Global projections indicate that by 2050, nearly half of the world’s population will be affected by myopia. Optical strategies based on the principle of peripheral myopic defocus, such as HAL, DIMS, MiYOSMART, Stellest, and DOT lenses, have proven to be the most effective non-invasive methods for slowing myopia progression in children. Clinical studies confirm that these lenses reduce axial eye elongation by 50–80% compared to standard single-vision lenses, while maintaining binocular balance and minimal adverse effects. HAL lenses achieve the most stable effect, whereas the DIMS design shows greater efficacy in children with slower myopic progression. Long-term studies demonstrate that these optical approaches do not induce a rebound effect after discontinuation and are safe for prolonged use.